If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(a + -14) + 5(a + -18) = 2 Reorder the terms: 6(-14 + a) + 5(a + -18) = 2 (-14 * 6 + a * 6) + 5(a + -18) = 2 (-84 + 6a) + 5(a + -18) = 2 Reorder the terms: -84 + 6a + 5(-18 + a) = 2 -84 + 6a + (-18 * 5 + a * 5) = 2 -84 + 6a + (-90 + 5a) = 2 Reorder the terms: -84 + -90 + 6a + 5a = 2 Combine like terms: -84 + -90 = -174 -174 + 6a + 5a = 2 Combine like terms: 6a + 5a = 11a -174 + 11a = 2 Solving -174 + 11a = 2 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '174' to each side of the equation. -174 + 174 + 11a = 2 + 174 Combine like terms: -174 + 174 = 0 0 + 11a = 2 + 174 11a = 2 + 174 Combine like terms: 2 + 174 = 176 11a = 176 Divide each side by '11'. a = 16 Simplifying a = 16
| Y^2-24y+144=-100 | | 2(4*s-16)-5*s=-5 | | 2y=58 | | 95+76=195 | | 4x=7x-1 | | y=4.25x-3 | | 8.1+3.8*h-5.6h=-7.2 | | X(7×10^4)/3=4×10^2 | | j-81=3 | | 9x-4=3x-11 | | 7(2v-1)+2=51 | | 81+21=120 | | 3y^2+11y+9=0 | | 21x=16x-7 | | 4.3*t-2.1*t-2.3=7.6 | | [x-6]=10 | | 12x+2=4x+1 | | (2x+39)=(7x+9) | | 8-3*x=17 | | 5x+3yx=10 | | [-4x]=16 | | 9x^4-25x=0 | | 8-3*x=16 | | -7x+3(5x+6)=82 | | 2b=19.6 | | -2(3x-4)+3(5x-1)= | | -5x+7=3x-5 | | 6+3x=8+-14 | | x^5-4x^4-32x^3= | | w+2.75=13.13 | | .24=log(x) | | 4-(x-5)=3(x-11) |